Prediction of stature from length of Ulna - An Anthropometric study on 100 Bangladeshi adult Muslim male of lower socioeconomic status group (Journal of Dhaka National Medical College & Hospital, 2017)
Background: Anthropometric study of bones conveys information about race, sex, age and height of a person as well as the effect of climatic, hereditary and nutritional status on stature and length of long bones which is very important for anatomist in the academic field. Stature of an individual can be estimated from measurements of long bones with the help of established formulae which plays an important role in medico-legal practice and thus length of long bones plays an important role in identifying unknown bodies.Objective: The present study was undertaken to measure the stature as well as some length of ulna and to determine whether there is any currelation between stature and length of ulna and to estimate the stature using respective multiplication factor and to asses the effectiveness of the above estimations by comparing the 'estimated values with the 'measured values.Material and Methods: It is descriptive type of study. Ulnar length with their stature were measured directly from the subjects by using Anthropometric spreading caliper, steel plate and measuring tape. The data were then statistically analyzed by computation to find out its normative value. Multiplication factors were estimated for estimating stature and comparisons were made between measured and estimated stature using paired "t" test.Place and period of study: The study was carried out with a total number of 100 Bangladeshi adult Muslim males of age between 25 to 30 years of lower socio-economic status group. The analyses were conducted in The Department of Anatomy of BSMMU, Dhaka during the study period of January 2006 to December 2006.Result: The mean measured values of the right and left ulnar length and the stature were 28.625 (± 1.170) cm, 28.235 (± 1.244) cm, and 163.70 (± 5.986) cm respectively. The multiplication factors were estimated for the ulnar lengths with the stature. Significant positive correlations were found between the stature and the ulnar length and the differences between the measured statures and the estimated statures were not statistically significant.Conclusion: This study will be helpful for the Anatomists, Anthropologists and also Forensic Medicine department of Bangladesh. For better result further study should be done on large samples of different socio-economic status groups, sexes and ethnic groups.J. Dhaka National Med. Coll. Hos. 2017, 23 (02): 23-27